2017
DOI: 10.18632/oncotarget.16854
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor (EGFR): A rising star in the era of precision medicine of lung cancer

Abstract: Lung cancer is a leading cause of cancer mortality worldwide. In tumors, the important role of noncoding RNA regulatory networks has been more and more reveal. EGFR has been identified as an oncogenic driver of NSCLC, especially activating mutations EGFR and its inhibition with specific TKIs can generate dramatic tumor responses. Studies have shown that EGFR plays significant roles in the progression of NSCLC. Subset analysis of the small proportion of patients with EGFR-mutant lung cancer showed a disease-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
136
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(139 citation statements)
references
References 98 publications
(65 reference statements)
2
136
0
1
Order By: Relevance
“…Functional experiments demonstrated that miR-539 exhibited as an oncogene in epithelial ovarian cancer [16] while as a tumour suppressor in other three types of cancers [17][18][19]. Besides that, EGFR, an oncogenic driver of lung cancer [20], was found as a target gene of miR-539 [21]. Based on these reason, we focused on investigating whether lidocaine functions to lung cancer cells through regulating miR-539.…”
Section: Introductionmentioning
confidence: 99%
“…Functional experiments demonstrated that miR-539 exhibited as an oncogene in epithelial ovarian cancer [16] while as a tumour suppressor in other three types of cancers [17][18][19]. Besides that, EGFR, an oncogenic driver of lung cancer [20], was found as a target gene of miR-539 [21]. Based on these reason, we focused on investigating whether lidocaine functions to lung cancer cells through regulating miR-539.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of entropy, SLC5A2 is involved in only two processes at L1, consolidating into a single aggregate at L886. A distinctly different behavior is identified for the epithelial growth factor receptor (EGFR) also being included in the multi-analyte panel tested in oncology indications [23,24]. EGFR as target, with major drugs including Cetuximab and Erlotinib, is embedded in 147 processes at L1, and shows one of the highest entropy courses of the given biomarker set.…”
Section: Information Content Of Biomarkersmentioning
confidence: 99%
“…Gefitinib and erlotinib were the first two reversible inhibitors of EGFR, followed by the second generation of inhibitors (afatinib, dacomitinib, neratinib and canertinib) designed to overcome clinical resistance [16]. The third generation of EGFR inhibitors (osimertinib) was developed to target the resistance produced by the T790M mutation [17], where the aberrant change of the normal threonine with a methionine as the gatekeeper residue increases the affinity for ATP [18]. Close to 60% of patients with melanoma harbor various mutations of B-RAF that cause activation of the MAPK pathway.…”
Section: Introductionmentioning
confidence: 99%